PARTISIPASI PEMUDA KARANG TARUNA SEHATI DALAM MEMBANGUN PROGRAM POSYANDU REMAJA DI DESA OEBELO KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Sara, Theodora Selvi; Selly, Frans K; Simbolon, Gallex (Education For All, 2024)
The objectives of this study are 1) To find out how the participation of Karang Taruna Sehati Oebelo Youth in building the Youth Posyandu Program 2) To find out the supporting and inhibiting factors of Karang Taruna SehatiOebelo Youth participation in the Youth Posyandu Program. This research method uses qualitative methods with a descriptive approach. The location of the study was in Oebelo Village, Central Kupang District, Kupang Regency. The subjects in the study were the head of Karang Taruna SehatiOebelo, a member of Karang Taruna SehatiOebelo and the head of a youth posyandu. Data collection using observation techniques, interviews and documentation studies. Data analysis techniques in the form of data collection, data reduction, data presentation and conclusions. The participation of the implementation stage, the participation of the Karang Taruna Sehati Youth is still less active. Participation in the utilization stage, after the Youth Posyandu Program has been implemented, there are benefits for Karang Taruna Sehati and for adolescents as program targets. The inhibiting factor for the participation of Karang Taruna Sehati Youth in the Youth Posyandu Program is that in addition to time issues, Conclusion The form of participation of the Karang Taruna Sehati Youth from planning, implementation to utilization has not fully run well because involvement in the implementation is only involved by 2 people in carrying out all activities at the place of implementation of the Youth Posyandu.